2018
DOI: 10.1088/1367-2630/aaec31
|View full text |Cite
|
Sign up to set email alerts
|

Incompressible polar active fluids in the moving phase in dimensions d > 2

Abstract: We study universal behavior in the moving (polar ordered) phase of a generic system of motile particles with alignment interactions in the incompressible limit for spatial dimensions d>2. Using a dynamical renormalization group analysis, we obtain the exact dynamic, roughness, and anisotropy exponents that describe the scaling behavior of such incompressible systems. This is the first time a compelling argument has been given for the exact values of the anomalous scaling exponents of a flock moving through a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…Furthermore, it can also be shown that for both "Malthusian" flocks [12] (that is, polar ordered dry active fluids without number conservation due to " birth and death" of the active particles) and incompressible polar ordered dry active fluids [13] , for all dimensions 2 ≤ d ≤ 4, these exponents are given by…”
Section: )mentioning
confidence: 99%
“…Furthermore, it can also be shown that for both "Malthusian" flocks [12] (that is, polar ordered dry active fluids without number conservation due to " birth and death" of the active particles) and incompressible polar ordered dry active fluids [13] , for all dimensions 2 ≤ d ≤ 4, these exponents are given by…”
Section: )mentioning
confidence: 99%
“…In other dimensions, in particular d = 3, little beyond the existence of anomalous hydrodynamics can be said. Interestingly, one system about which more can be said is incompressible flocks [12,13]; i.e., polar ordered active fluids in which the density is fixed, either by an infinitely stiff equation of state, or by long-ranged forces. For these systems, it is possible to obtain exact exponents for all spatial dimensions; as for number conserving systems with density fluctuations, these prove to be anomalous for spatial dimensions d in the range 2 ≤ d ≤ 4.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the theoretical situation is therefore still quite unsatisfactory: we only have the scaling laws for flocks if they either are incompressible (which requires either infinitely strong, or infinitely ranged, interactions), or in d = 2. And in the cases in which we do know the exponents, their values are either the canonical ones (I.1) [12,14], or those from the (1+1)-dimensional KPZ model [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact biological or environmental factors that trigger such transition depend on the particular species, physicists have successfully used the theory of dry-active matter to study disorder-order phase transition in these systems [6,7]. Theoretical studies have revealed that for an incompressible flock, where we can ignore density fluctuations, the order-disorder phase transition is continuous [8][9][10].…”
mentioning
confidence: 99%